(untitled) (XXI Century. Spanish Literature and Culture, 2004)
This article focuses on the most noticeable works of published poetry within the Spanish literary milieu of 2007. In addition to examining the contributions of authors already established as innovators of their craft, it takes a look at several anthologies and highlights the distinct tendencies that characterise the poetic evolution taking place in Spain today